Radio-echo sounding in Antarctica, 1971–72 - Evans, S.; Drewry, D. J.; Robin, G. de Q. (Polar Record, 1972)
A third field season in the joint research programme of the Scott Polar Research Institute (SPRI) and the United States National Science Foundation (NSF) was carried out between November 1971 and January 1972. For accounts of previous work in this programme, see Polar Record (1968); Evans and Smith, (1970); and Robin and others (1970). The personnel from SPRI working in the field during the past season were S. Evans, C. H. Harrison, D. J. Drewry, G. K. A. Oswald, M. R. Gorman, and (from the University of Gent and Expéditions Antarctiques Belges) H. Decleir. A. Clayton and J. Whittington of the SPRI staff assisted in data reduction.